The nucleotide sequence of the cytoplasmic 5S rRNA from the horsetail, Equisetum arvense. - Ulbrich, N (1984)
Using 3'- and 5'-end labelling sequencing techniques, the following sequence for the cytoplasmic 5S rRNA of the horsetail Equisetum arvense could be determined: (sequence in text). This sequence exhibits all features expected for higher plant cytoplasmic 5S rRNAs, and can be fitted to the secondary structure model for 5S rRNA proposed by De Wachter et al. (15).